The effect of juggling on the proprioceptive and attentional abilities among older women - Jakub Malik; Natalia Główka; Wojciech Jelonek; Janusz Maciaszek (Frontiers Media S.A., 2024)
BackgroundAge-related changes in attentional abilities can lead to a decline in body segment awareness in space. However, studies have reported that physical activity can improve proprioception among older adults, although proven activities with this potential are limited. Juggling is a promising activity for enhancing proprioception, as it requires high levels of attention and sensory precision. The first hypothesis posited that a juggling intervention would positively impact ipsilateral and contralateral elbow joint position matching without visual input. The second hypothesis suggested a correlation between cognitive abilities and joint position sense efficiency.MethodsA total of 20 older women (mean age: 69.95 ± 4.58) participated in a repeated-measures study using a Latin square design. Measurements were taken at three time points (baseline, post-juggling, and control). Ipsilateral and contralateral elbow joint position matchings without visual or verbal feedback of accuracy were used to assess proprioception. Attention and reaction time variables were measured using the Vienna Test System protocols.ResultsAlthough significant changes were observed between baseline and subsequent time points in joint position sense accuracy, no specific effect of juggling was detected. Low and medium correlations were found between decision time and the variability of choice reaction time with contralateral accuracy. For ipsilateral accuracy, a relationship was observed only with handedness. No correlations were found between attention test scores and joint position sense accuracy.ConclusionThe study did not demonstrate a significant effect of juggling on position-matching ability. However, cognitive abilities such as decision speed and the stability of choice reaction time may play a role in enhancing position-matching in older women.Clinical trial registrationClinicalTrials.gov, identifier NCT06108713.